The importance of digital marketing and fintech based on payment gateway to improve MSMEs performance and sustainability - Seta, Vivian Evan; Sari, Ratna Purnama; Nusron, Lulu Amalia (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2025)
This study aims to examine whether digital marketing, payment gateway-based fintech, and financial attitudes affect business performance and business sustainability. Data were obtained by distributing 146 questionnaires directly (offline) and via Google Forms (online) to MSMEs in the Special Region of Yogyakarta. The resulting data is processed using the Structural Equation Model (SEM) with Smart PLS. Some of the findings of previous studies partially tested the effect of digital marketing, payment gateway-based fintech, and financial attitudes. This study develops the results of earlier studies by adding a structurally tested sustainability variable. The analysis results show that digital marketing, payment gateway-based fintech affect business performance. Furthermore, performance affects business sustainability. However, a financial attitude does not affect business performance. This research implies that government support is still needed so that MSMEs can take advantage of digital marketing and financial technology to compete in the global market. Keywords: Digital marketing; Fintech; Financial attitude; Performance; Sustainability.